Building a global immune system. Issue 4 (30th November 2022) - Lipkin, W. I.; Briese, T.
ABSTRACT: The COVID-19 pandemic exposed global vulnerabilities to emerging infectious diseases, heralded by earlier outbreaks, that did not result in appropriate investments in surveillance, international collaboration, and response. We propose specific steps that should be taken to reduce future risks to public health, economic and political stability, and food security.